Probing the Dual Role of Ca2+ in the Allochromatium tepidum LH1–RC Complex by Constructing and Analyzing Ca2+-Bound and Ca2+-Free LH1 Complexes - Mei-Juan Zou; Shuai Sun; Guang-Lei Wang; Yi-Hao Yan; Wei Ji; Zheng-Yu Wang-Otomo; Michael T. Madigan; Long-Jiang Yu (Biomolecules)
The genome of the mildly thermophilic hot spring purple sulfur bacterium, Allochromatium (Alc.) tepidum, contains a multigene pufBA family that encodes a series of α- and β-polypeptides, collectively forming a heterogeneous light-harvesting 1 (LH1) complex. The Alc. tepidum LH1, therefore, offers a unique model for studying an intermediate phenotype between phototrophic thermophilic and mesophilic bacteria, particularly regarding their LH1 Qy transition and moderately enhanced thermal stability. Of the 16 α-polypeptides in the Alc. tepidum LH1, six α1 bind Ca2+ to connect with β1- or β3-polypeptides in specific Ca2+-binding sites. Here, we use the purple bacterium Rhodospirillum rubrum strain H2 as a host to express Ca2+-bound and Ca2+-free Alc. tepidum LH1-only complexes composed of α- and β-polypeptides that either contain or lack the calcium-binding motif WxxDxI; purified preparations of each complex were then used to test how Ca2+ affects their thermostability and spectral features. The cryo-EM structures of both complexes were closed circular rings consisting of 14 αβ-polypeptides. The Qy absorption maximum of Ca2+-bound LH1 (α1/β1 and α1/β3) was at 894 nm, while that of Ca2+-free (α2/β1) was at 888 nm, indicating that Ca2+ imparts a Qy transition of 6 nm. Crucially for the ecological success of Alc. tepidum, Ca2+-bound LH1 complexes were more thermostable than Ca2+-free complexes, indicating that calcium plays at least two major roles in photosynthesis by Alc. tepidum—improving photocomplex stability and modifying its spectrum.